Efeitos de doses de localização do fósforo na cultura do tomateiro (Lycopersicum esculentum Mill) - Baumgartner, José Geraldo; Guimarães de Andrade Landell, Marcos; Gabino Crispin Churata-Masca, Manuel; Hiroce, Ruter; Campos de Araújo, Jairo Augusto (Revista Ceres, 2025)
Two experiments were carried out at Jaboticabal, State of São Paulo, Brazil, to study the effects of phosphorus fertilization on tomato.